2007
DOI: 10.1002/elan.200603805
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor Based on Self‐Assembling Glucose Oxidase and Dendrimer‐Encapsulated Pt Nanoparticles on Carbon Nanotubes for Glucose Detection

Abstract: A novel amperometric glucose biosensor based on layer-by-layer (LbL) electrostatic adsorption of glucose oxidase (GOx) and dendrimer-encapsulated Pt nanoparticles (Pt-DENs) on multiwalled carbon nanotubes (CNTs) was described. Anionic GOx was immobilized on the negatively charged CNTs surface by alternatively assembling a cationic Pt-DENs layer and an anionic GOx layer. Transmission electron microscopy images and z-potentials proved the formation of layer-by-layer nanostructures on carboxyl-functionalized CNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 35 publications
1
37
2
Order By: Relevance
“…As shown in Fig. 2a, CoHCF was successfully deposited onto ITO-(PVS/PAMAM-Au) 3 electrodes by potential cycling, with the cathodic and anodic peak currents increasing linearly with the number of cycles. The deposited mediator was characterised by cyclic voltammetry in 0.1 M NaPBS (pH 7.0) supporting electrolyte, the anodic and cathodic peak currents being a linear function of the square root of the scan rate, as shown in Fig.…”
Section: Preparation Of An Electroactive Nanostructured Membrane (Enmmentioning
confidence: 96%
See 4 more Smart Citations
“…As shown in Fig. 2a, CoHCF was successfully deposited onto ITO-(PVS/PAMAM-Au) 3 electrodes by potential cycling, with the cathodic and anodic peak currents increasing linearly with the number of cycles. The deposited mediator was characterised by cyclic voltammetry in 0.1 M NaPBS (pH 7.0) supporting electrolyte, the anodic and cathodic peak currents being a linear function of the square root of the scan rate, as shown in Fig.…”
Section: Preparation Of An Electroactive Nanostructured Membrane (Enmmentioning
confidence: 96%
“…The last step for ITO-(PVS/PAMAM-Au) 3 @CoHCF build-up was to use the system ITO-(PVS/PAMAM-Au) 3 as working electrode to electrochemically modify the PAMAM-Au surface. We previously showed that ITO-(PVS/PAMAM-Au) 3 structures are suitable for biosensors and electrocatalysis owing to their low capacitive and high Faradaic currents associated with low ohmic drop [8].…”
Section: Preparation Of An Electroactive Nanostructured Membrane (Enmmentioning
confidence: 99%
See 3 more Smart Citations